If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(6 + -1x) = -22 3x + (6 * -1 + -1x * -1) = -22 3x + (-6 + 1x) = -22 Reorder the terms: -6 + 3x + 1x = -22 Combine like terms: 3x + 1x = 4x -6 + 4x = -22 Solving -6 + 4x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4x = -22 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = -22 + 6 4x = -22 + 6 Combine like terms: -22 + 6 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 3.7x-3.18=12.508 | | 7x^3-2x^2-35x+10= | | 2x+tanx=0 | | 7a^4-51a^2+14=0 | | 5.14x+8.96=2.9x | | 6x^2+10-5= | | 3x-4=2x^2+x+1 | | y=27.5(109.5)-1635.75 | | 4(x-30)=20 | | 16=.5*3(a+4) | | 1/2(y-1/5)=1/5(y+2) | | 23+2=3 | | i=200+0.11+2 | | -14=16x+1 | | 8x=-6 | | 92=-4(1-3x) | | p=68+145 | | 5x-36-11x=3x+3x | | 3x-5y=-47 | | x/2-1=x/7+4 | | -5x-19y=3.5 | | 4(m-5)=5(m-7) | | 1+2x=2(2x+6)-3(x-1) | | 6x-700=4x+500 | | 11-5x=17+5(2-x) | | 4x-2(5-x)=14 | | -4.2-5x=4.8 | | 5x+12+4x+11=2x+2 | | .3x-1=11 | | 9(-9x+4)=-3(6x+9) | | -3(1-4a)+2a=95 | | -16=d-21 |